Perspectives for Germany's Energy Policy - Claudia Kemfert; Jochen Diekmann (Weekly Report, 2006)
For various reasons, the policies governing the energy sector have a central role to play in Germany. Thus, for example, competition on the electricity and gas markets will have to be increased considerably in the course of the market's liberalization. At the same time, a secure supply of energy must also be ensured, in other words, the matters of preventing short-term power outages while ensuring the long-term availability of energy resources must be dealt with. Last but not least, the environmental compatibility of the energy sector must be improved, in particular with a view towards global climate change. In the coming years, considerable replacement investments will need to be made, in particular where the electricity sector is concerned. That is why any decision taken today in the context of energy policy is important for the future. Energy policy must pursue the objectives of security of supply, competitiveness and environmental compatibility, giving them equal rank. In this context, it is necessary to establish specific and binding targets for the reduction of greenhouse gas emissions, both at the international and at the national level. In order to attain these objectives, it will be absolutely necessary to save energy, to increase energy efficiency, to phase out the use of high-emission energy carriers and, in particular, to more intensively use renewable energies. Furthermore, the capture and storage of carbon (CCS) could contribute to reducing the output of gases that have a detrimental effect on global climate. While subsidies for the German hard coal mining industry must be reduced further, the research into and development of CCS technologies should be granted greater support. The consensus reached as to nuclear power plants should not be taken as an excuse to have old nuclear facilities operate for a longer time while reducing the life cycles of nuclear power plants that were built more recently at the same time. Increasing the amounts of electrical power generated in safe nuclear power plants for a limited period of time could provide the sector with the flexibility it needs while achieving an energy mix that is sustainable in the long term. In order to improve energy efficiency and to increase the use of renewable energies, specifically targeted political measures need to be taken. In this way, it will be possible to open up new market potential that also promises competitive advantages in the long term. The coalition agreement signed by the new Federal German Government sets ambitious goals which need to be implemented promptly.
Keywords: 330